Kebijakan Pembatasan Sosial Berkala: Prediksi Sikap Masyarakat Terhadap Telemedis Selama Pandemi COVID-19 - Tiar Anindya Putri (Jurnal Informasi dan Teknologi, 2022)
Telemedicine can provide routine care services without the risk of contracting Covid-19 in online way in the government's policy for social restrictions and adaptation of new habits stages. This study was intended to assess attitudes in the direction of telemedicine at some stage in periodical social restrictions in Indonesia, then examine the general public's willingness to use the service within the future, and also examine the extent to which respondent have changed their minds about the service. This study uses two statistical analysis approaches. The first approach was a cross-sectional, descriptive, and correlational study conducted among adults aged over 19 years using social media networks. Then the second approach is Ordered Logistic Regression models on two questionnaire items for the dependent variable, specifically predicting willingness to apply telemedicine within the future and predicting changes in thoughts about telemedicine. Sixty-four percent of respondents agree and strongly agree that they need to use telemedicine during the periodical social restriction period of the COVID-19 pandemic. However, despite the availability of telemedicine during the COVID-19 pandemic, 46.92% of respondents tend to still like to go to clinics or hospitals. A total of 24.64% of respondents were hesitant to go to a clinic or hospital, and 28.44% of respondents were hesitant to go to a clinic or hospital. This makes telemedicine in Indonesia not yet considered a necessity, but is still considered the first solution that can be done on a periodic basis.